Well-Being, Isolation, and Lockdowns in the UK - José Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2025)
Social connection is a key determinant of emotional well-being, yet the role of solitude in shaping both momentary affect and overall life satisfaction remains understudied. This paper investigates how being alone while engaging in daily activities relates to subjective well-being, using rich time-use diary data from the UK covering four distinct periods: pre-pandemic (2015–2016), the Covid-19 lockdowns (2020–2021), the relaxation phase (2021), and the post-pandemic period (2023). We find that being alone is negatively associated with momentary enjoyment, particularly in the post-pandemic period, but not during lockdowns or the initial relaxation phase, suggesting that the emotional cost of solitude depends on its perceived voluntariness and social norms. The enjoyment penalty is strongest for leisure and unpaid work episodes, and most pronounced among remote workers. We also document a negative association between full-day solitude and overall life satisfaction, but only during the relaxation phase, suggesting that solitude can impose both short-term and longer-term costs of well-being, depending on the social context and type of activity.
Keywords: J16; J22; 330; lockdown; COVID-19; life satisfaction; instant enjoyment; well-being; time use data